WE5.2 Safety of in-hospital delay to appendicectomy in acute appendicitis: a retrospective study. (9th August 2022) - Claydon, Oliver; Down, Billy; Kumar, Sidharth
Abstract: Aims: In many hospitals the availability of operating theatres and access to senior surgical and anaesthetic support diminishes during night hours. Therefore urgent surgery is sometimes postponed until the following morning rather than performed overnight, if judged to be safe. We aim to determine if a delay to laparoscopic appendicectomy in cases of acute appendicitis of over 12 hours, analogous to an overnight delay, is correlated to worse patient outcomes. Our primary outcome was delayed discharge from hospital. Our secondary outcomes were appendicitis severity, conversion, and post-operative complications. Methods: We undertook a retrospective review of the medical records of patients who underwent laparoscopic appendicectomy at a UK district general hospital between 01/01/2018 and 30/08/2019. For each patient clinical and demographic information; and times of hospital admission, surgery, and discharge; were collected. Delayed discharged was defined as 'time to discharge' >24 hours. Results: 506 patients were included. In 144 patients (28.5%) 'time to surgery' was under 12 hours; in 362 patients (71.5%) 'time to surgery' was over 12 hours. 362 patients (71.5%) had a delayed discharge. 303 patients (59.9%) had simple appendicitis; 143 patients had severe appendicitis (28.3%); 60 patients had a macroscopically normal appendix (11.9%). No statistically significant association between 'time to surgery' and delayed discharge, appendicitis severity, conversion or 30 day re-presentations was observed. Conclusions: Time from admission to start of appendicectomy did not affect patient outcomes. Short in-hospital delays to appendicectomy, for example an overnight delay, may be safe in certain patients, taking account of clinical judgement.